Lactate measurement by neurochemical profiling in the dorsolateral prefrontal cortex at 7T: accuracy, precision, and relaxation times. Issue 6 (14th November 2019) - Dehghani, Masoumeh; Do, Kim Q.; Magistretti, Pierre; Xin, Lijing
Abstract : Purpose: This assesses the potential of measuring lactate in the human brain using three non‐editing MRS methods at 7T and compares the accuracy and precision of the methods. Methods: 1 H MRS data were measured in the right dorsolateral prefrontal cortex using a semi‐adiabatic spin‐echo full‐intensity acquired localized sequence with three different protocols: (I) TE = 16 ms, (II) TE = 110 ms, and (III) TE = 16 ms, TI = 300 ms. T 1 and T 2 relaxation times of lactate were also measured. Simulated spectra were generated for three protocols with known concentrations, using a range of spectral linewidths and SNRs to assess the effect of data quality on the measurement precision and accuracy. Results: Lactate was quantified in all three protocols with mean Cramér‐Rao lower bound of 8% (I), 13% (II), and 7% (III). The T 1 and T 2 relaxation times of lactate were 1.9 ± 0.2 s and 94 ± 13 ms, respectively. Simulations predicted a spectral linewidth‐associated underestimation of lactate measurement. Simulations, phantom and in vivo results showed that protocol II was most affected by this underestimation. In addition, the estimation error was insensitive to a broad range of spectral linewidth with protocol I. Within‐session coefficient of variances of lactate were 6.1 ± 7.9% (I), 22.3 ± 12.3% (II), and 5.1 ± 5.4% (III), respectively. Conclusion: We conclude that protocols I and III have the potential to measure lactate at 7T with good reproducibility, whereas the measurement accuracy and precision depend on spectral linewidth and SNR, respectively. Moreover, simulation is valuable for the optimization of measurement protocols in future study design and the correction for measurement bias.